Implementasi Prinsip Good Governance Pada Lembaga Pengelolaan Zakat BAZNAS Kota Gorontalo - Sudirman Sudirman (Universitas Islam Negeri Alauddin Makassar, 2019)
This study aims to analyze the implementation of the principles of good governance in the management of zakat in the National Zakat Agency (BAZNAS) of Gorontalo City. This research is qualitative research. Data collection techniques are carried out through interviews, observation, and documentation.The results of the study show that the implementation of the principles of Good Governance in the BAZNAS Institute of Gorontalo City is sufficient, both in the aspects of transparency, justice, and responsibility as well as on the legal aspects. Then, specifically in the aspect of accountability, it has not been fully in accordance with the Accounting Standard Statement PSAK 02 revision 2009. In this study it was found that the cash outflow report has not referred to ED PSAK found that BAZNAS Gorontalo City only reported 2 activities, namely operational and investment activities, while in the aspect of funding has not been raised in the financial statements